Distribution of porosity surrounding a microfiber in cement paste - He, Shan (2024)
This study investigates the microstructural changes of cement paste due to the inclusion of polymeric microfiber at different water-to-cement (w/c) ratios. A procedure to quantify the porosity of epoxy impregnated interfacial transition zone (ITZ) is also presented. Results show that the microstructures of the ITZ beneath and above a microfiber, with respect to the gravity direction, are largely different. Though the ITZ at both sides of the fiber are more porous than the bulk matrix, the porosity of the lower ITZ (i.e., the ITZ beneath a fiber) is significantly higher than the upper side (i.e., the ITZ above a fiber). This difference can be attributed to the combined effects of fiber on the initial packing of surrounding cement grains and on the settlement of the fresh mixture. The porosity gradients of the upper ITZs are found to be nearly identical for all the tested w/c ratios, while the porosity gradients of the lower ITZs become steeper when the w/c is higher. The lower side is also found to be the preferred location for the precipitation of calcium hydroxide crystals. Results of energy-dispersive X-ray spectroscopy (EDS) and nano-indentation analyses confirm that the chemical and mechanical properties of the ITZ are also asymmetric.